Urban Cost Performance and Industrial Agglomeration: City-Level Evidence from China. Issue 7 (27th May 2020) - Zeng, Lixia; Chen, Meilan; Zhang, Fangfang
ABSTRACT: This study focuses on the prefecture-level cities in various provinces and autonomous regions in China, collects economic data from 2009 to 2014, and analyzes the cost efficiency in each region. To fill in the gap in the previous research, the present study analyzes the change trend of cost performance among Chinese prefecture-level cities in different years and explores the relationship between urban cost performance and industrial agglomeration. Results show that the average score of cost efficiency score of all prefecture-level cities is 0.694. The distribution of production efficiency in each region shows a downward trend from 2009 to 2010 and a growth trend after 2012. Furthermore, this study explores the influence of the rationalization of industrial structure and the industrial structure supererogation on the cost efficiency of urban economic activities. The results revealed that the more reasonable distribution of industrial structure in the city is associated with a higher level of cost savings of urban economic development.